Preparation and application of chitosan modified attapulgite nucleic acid adsorption rod
By combining chitosan-modified attapulgite with polyvinylidene fluoride and N-methylpyrrolidone to prepare nucleic acid adsorption rods, the problems of cumbersome, high cost and unstable output of existing nucleic acid extraction methods have been solved, and the Efficient and stable nucleic acid adsorption effect and cost reduction.
Patent Information
- Application Number
- CN202411437192.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing nucleic acid extraction methods have problems such as cumbersome steps, long time, high cost, and easy to be contaminated by organic reagents. Moreover, magnetic adsorbent materials are prone to agglomeration and settlement during adsorption and transfer, resulting in unstable sample loss and yield in the extraction process.
Chitosan-modified attapulgite was prepared into nucleic acid adsorption rods through polyvinylidene fluoride and N-methylpyrrolidone. This material was used for nucleic acid extraction, reducing the amount of material, retaining the structure, and improving adsorption efficiency and stability.
It achieves good nucleic acid adsorption quality and stable adsorption effect, reduces the dosage of chitosan-modified attapulgite (28.6% reduction), has lower cost, is easy to carry, and is convenient and efficient.
Smart Images

Figure CN119327428A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biotechnology, and in particular to the preparation and application of a chitosan-modified attapulgite nucleic acid adsorption rod. Background Art
[0002] Foodborne diseases have caused huge public health, economic and social burdens around the world. Rapid and accurate detection of foodborne pathogens is an important means of preventing and treating various foodborne diseases, and rapid acquisition of high-quality pathogen nucleic acids is a prerequisite for efficient and accurate nucleic acid detection. Current nucleic acid extraction methods have problems such as cumbersome steps, long time consumption, high cost, and easy contamination by organic reagents.
[0003] Liquid phase extraction is simple to operate and low in cost. It is an effective method for nucleic acid extraction, but it has many problems, such as requiring a large amount of organic solvents, more samples, long separation time, susceptibility to contamination, and susceptibility to nucleic acid degradation. In addition, liquid phase extraction based on organic solvent extraction can significantly increase the risk of residual amplification inhibitors. Compared with liquid phase separation, nucleic acid solid phase extraction can relatively reduce the use of organic reagents, and the operation is simpler and more efficient. Nanomaterial-based nucleic acid extraction methods usually require cumbersome centrifugation, filtration and other operations. Although the magnetic adsorption materials currently popular in the market can realize the automation of the extraction process, magnetic beads have agglomeration and sedimentation during the adsorption and transfer process, resulting in sample loss and unstable yield during the extraction process. In addition, in order to avoid cross-contamination of samples, nucleic acid extraction materials are generally disposable, and the preparation cost should be minimized during routine testing.
[0004] Patent CN116393105A discloses a method for adsorbing nucleic acids using chitosan-modified attapulgite. However, during use, the chitosan-modified attapulgite has a loose structure, and the subsequent analysis and processing methods are cumbersome, making it unsuitable for carrying and immediate DNA extraction. In addition, the chitosan-modified attapulgite dispersion is prone to sedimentation. During use, the amount of chitosan-modified attapulgite is uneven, resulting in large errors. At the same time, the modified attapulgite powder is also inconvenient to carry and the nucleic acid adsorption effect is unstable.
[0005] On this basis, the preparation of chitosan-modified attapulgite is complicated and costly, and improving the utilization rate of chitosan-modified attapulgite has extremely high economic value. Therefore, it is urgent to find a material and method that is more convenient to use, more stable in effect, lower in cost and has good extraction effect. Summary of the invention
[0006] In order to solve the above problems, the present invention prepares chitosan-modified attapulgite into nucleic acid adsorption rods by using polyvinylidene fluoride and N-methylpyrrolidone. The chitosan-modified attapulgite nucleic acid adsorption rods of the present invention have good adsorption quality and stable adsorption effect.
[0007] In the present invention, the good adsorption quality of nucleic acid refers to the extracted nucleic acid A 260 / A 280 It is 1.7 to 1.9.
[0008] The first object of the present invention is to provide a chitosan-modified attapulgite nucleic acid adsorption rod, the preparation method of which comprises:
[0009] Chitosan-modified attapulgite, polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) are mixed and ground according to a dosage ratio of 50-60 mg: 5-8 mg: 100-150 μL to obtain a mixture; the mixture is coated on a metal wire to obtain an adsorption rod; and the mixture is solidified to obtain a chitosan-modified attapulgite nucleic acid adsorption rod.
[0010] In one embodiment, the material thickness of the adsorption rod is 100-150 μm.
[0011] In one embodiment, the metal wire includes, but is not limited to, stainless steel wire, copper wire, and aluminum wire.
[0012] In one embodiment, the method for preparing the metal wire is: ultrasonically cleaning the metal wire in acetone, ethanol and ultrapure water in sequence for 10 to 20 minutes, and drying at 60 to 65° C. for 2 to 3 hours.
[0013] In one embodiment, curing is performed by heating the adsorption rod at 75-85° C. for 30-40 minutes.
[0014] In one embodiment, the amount of chitosan-modified attapulgite in each chitosan-modified attapulgite nucleic acid adsorption rod is 0.7 mg.
[0015] The second object of the present invention is to provide the use of any of the above-mentioned chitosan-modified attapulgite nucleic acid adsorption rods in adsorbing nucleic acids.
[0016] The third object of the present invention is to provide a method for simultaneously improving the nucleic acid adsorption amount and adsorption quality of chitosan-modified attapulgite nucleic acid adsorption rods, the method comprising:
[0017] Chitosan-modified attapulgite, polyvinylidene fluoride and N-methylpyrrolidone are mixed and ground according to a dosage ratio of 50-60 mg: 5-8 mg: 100-150 μL to obtain a mixture; the mixture is coated on a metal wire to obtain an adsorption rod; and the mixture is solidified to obtain a chitosan-modified attapulgite nucleic acid adsorption rod.
[0018] In one embodiment, the metal wire includes stainless steel wire, copper wire, or aluminum wire.
[0019] In one embodiment, the material thickness of the adsorption rod is 100-150 μm.
[0020] In one embodiment, curing is performed by heating the adsorption rod at 75-85° C. for 30-40 minutes.
[0021] Beneficial effects of the present invention:
[0022] The present invention prepares chitosan-modified attapulgite as a nucleic acid adsorption rod by using polyvinylidene fluoride and N-methylpyrrolidone. The chitosan-modified attapulgite nucleic acid adsorption rod of the present invention has high adsorption efficiency, good quality and stable adsorption effect on the basis of reducing the amount of materials and retaining the structure of chitosan-modified attapulgite. The content of chitosan-modified attapulgite in the chitosan-modified attapulgite nucleic acid adsorption rod of the present invention is controllable, and each is 0.7 mg, which further reduces the error caused by operation; compared with the prior art CN116393105A, the amount of chitosan-modified attapulgite is lower (0.9 mg), the amount is reduced by 28.6%, the cost is lower, and it is easy to carry, convenient and efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of extracting genomic DNA using chitosan-ATP (chitosan modified attapulgite) nucleic acid adsorption rods.
[0024] Figure 2 (a) Optimization of preparation conditions of nucleic acid adsorption rods. Optimization of the ratio of binder and solvent addition to optimize DNA adsorption rate. Figure 2 (b) Graph showing the optimized DNA adsorption rate for the ratio of material and binder addition.
[0025] Figure 3 This is the X-ray diffraction (XRD) characterization diagram of chitosan-ATP-PVDF (chitosan modified attapulgite-polyvinylidene fluoride).
[0026] Figure 4 This is the Fourier transform infrared spectrum (FTIR) analysis diagram of chitosan-ATP-PVDF.
[0027] Figure 5 This is the zeta potential analysis diagram of chitosan-ATP-PVDF.
[0028] Figure 6 This is a scanning electron microscope (SEM) image of chitosan-ATP-PVDF.
[0029] Figure 7 It is the electrophoresis diagram of genomic DNA, in which, band 1: genomic DNA of Staphylococcus aureus; band 2: genomic DNA of Escherichia coli; band 3: genomic DNA of Salmonella.
[0030] Figure 8 Extraction of genomic DNA for qPCR analysis using nucleic acid adsorption rods. Figure 8(a) is the amplification curve of Escherichia coli genomic DNA, Figure 8 (b) is the linear fitting curve of E. coli genomic DNA amplification, Figure 8 (c) is the amplification curve of Staphylococcus aureus genomic DNA. Figure 8 (d) is the linear fitting curve of Staphylococcus aureus genomic DNA amplification. Figure 8 (e) is the amplification curve of Salmonella genomic DNA, Figure 8 (f) is the linear fitting curve of Salmonella genomic DNA amplification, and NTC is the negative control without target. DETAILED DESCRIPTION
[0031] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0032] Schematic diagram of chitosan-ATP nucleic acid adsorption rod for extracting genomic DNA Figure 1 shown.
[0033] 1. Materials and reagents:
[0034] Attapulgite (ATP) (325 mesh, produced by Jiangsu Xuyi Oubaite Company); fish sperm DNA, agarose, column-based bacterial genomic DNA extraction kit (Shanghai Bioengineering Co., Ltd. No. B518255Ezup), magnetic bead-based bacterial genomic DNA extraction kit (Shanghai Bioengineering Co., Ltd. No. B518725), N-methyl-2-pyrrolidone (NMP) (Shanghai Bioengineering Co., Ltd.); DNA loading buffer (instant view TM Red fluorescent DNA loading buffer, 6× containing bromophenol blue (Shanghai Biyuntian Co., Ltd.); anhydrous ethanol and acetone (analytical grade, Sinopharm Chemical Reagent Co., Ltd.); PVDF, glacial acetic acid, chitosan (deacetylation degree ≥ 95%, viscosity 100-200 mPa.s) (analytical grade, Shanghai Aladdin Reagent Co., Ltd.); anhydrous sodium acetate (analytical grade, Beijing Inokai Technology Co., Ltd.); ultrapure water used in the experiment was purified using a Milli-Q A10 filtration system (18.2 MΩ·cm); Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 25922, and Salmonella ATCC 14028: preserved in the Food Safety and Quality Control Research Center of the School of Food Science and Technology, Jiangnan University. Stainless steel needle (0.40×40 mm, Wujiang Yunlong Medical Instrument Co., Ltd.); 2× TaqMan Fast qPCR premix (Shanghai Bioengineering Co., Ltd.); all oligonucleotides were synthesized, modified, and purified by Shanghai Shengong Bioengineering Co., Ltd.
[0035] 2. Instruments and equipment:
[0036] HWCL-1 heating magnetic stirrer (Zhengzhou Great Wall Science and Technology Co., Ltd.); TUS-200P oscillating constant temperature metal bath (Shanghai Yiheng Scientific Instrument Co., Ltd.); SS-5452 small high-speed centrifuge (Eppendorf, Germany); Tanon5200 fully automatic chemiluminescence image analysis system (Shanghai Tianneng Life Science Co., Ltd.); K5500 ultra-micro spectrophotometer (Hangzhou Ruixi Technology Co., Ltd.); LS-B50L sterilizer (Shanghai Medical Nuclear Instrument Factory); D2 PHASER X-ray diffractometer (Bruker AXS Co., Ltd., Germany); IS10 Fourier transform infrared spectrometer (Nicolet, USA); Quanta250FEG field emission scanning electron microscope (FEI, USA); Nano ZS nanoparticle size and Zeta potential analyzer (Malvern, UK); XLX-096D 96-well four-color real-time fluorescence quantitative qPCR instrument (Jiangsu Xinlanxin Biotechnology Co., Ltd.); scientz-IID ultrasonic cell disruptor (Ningbo Xinzhi Biotechnology Co., Ltd.); AB104-N electronic analytical balance (Mettler Toledo Instrument (Shanghai) Co., Ltd.); clean bench and SHP-150 biochemical incubator (Shanghai Senxin Experimental Instrument Co., Ltd.).
[0037] 3. Detection method
[0038] (1) Preparation method of chitosan modified attapulgite:
[0039] 10 g of attapulgite powder (>325 mesh) was mixed with 100 mL of 10 wt% HCl, stirred and reacted at 70 ° C for 2 h, filtered, and the filter residue was washed with deionized water to pH = 6.0. The washed filter residue was placed in an oven at 105 ° C and dried for 12 h, and then ground through a 325 mesh standard sieve to obtain acid-activated attapulgite powder.
[0040] 0.2 g chitosan and 2 g acid-activated attapulgite were added to 300 mL 1 wt% hydrochloric acid, stirred at 60 ° C for 24 h, and then 1.25 mol / L NaOH was added dropwise until neutral. The neutralized solution was placed in an oven at 105 ° C for 12 h, and then ground through a 325 mesh standard sieve to obtain chitosan-modified attapulgite powder.
[0041] (2) Bacteria treatment method:
[0042] Bacteria collection: Inoculate the bacterial solution into 3 mL of sterilized tryptic soy broth (TSB) and culture at 37°C and 160 rpm for 18 h. Take 1 mL of overnight cultured bacteria in a 1.5 mL centrifuge tube, centrifuge at 8,000 rpm for 1 min at room temperature, discard the supernatant, and collect the bacteria.
[0043] Bacterial lysis: Add 100μL Buffer Digestion, 80μL lysozyme solution (20mg / mL) and 2μL lysostaphin solution (2mg / mL) to resuspend the bacterial solution, and place in a 37℃ water bath for 30min. Add 20μL Proteinase K solution and oscillate to mix. To obtain RNA-free DNA, add 20μL RNase A (10mg / mL) after the water bath and place at room temperature for 2-5min. Place in a 56℃ water bath for 30min until the cells are completely lysed. Add 200μL Buffer BD, mix thoroughly by inversion, and place in a 70℃ water bath for 10min until the solution becomes clear, and obtain bacterial lysis solution.
[0044] (2) Chitosan-modified attapulgite nucleic acid adsorption and analysis method:
[0045] Adsorption of modified attapulgite on bacterial genomic DNA: 30 mg of attapulgite sample was added to 1 mL of ultrapure water to prepare a attapulgite sample suspension. Then, 30 μL of attapulgite sample suspension (30 mg / mL) and bacterial lysate (400 μL) were mixed with 70 μL of acetic acid-sodium acetate buffer solution. The pH of the system was 5, and Na + The concentration is 80mM and the total system is 500μL. The mixture is shaken at 1000r / min in a constant temperature shaking incubator and centrifuged at 8000×g for 10min. The DNA concentration in the supernatant is measured using a micro-nucleic acid quantifier. The amount of adsorbed DNA can be calculated by the difference between the amount of added DNA and the amount of supernatant DNA.
[0046] Desorption of bacterial genomic DNA by modified attapulgite: The precipitate was washed with 70% ethanol, dried after centrifugation, and the DNA was eluted with 100 μL of elution solution. The nucleic acid concentration in the elution solution was measured using a micro-nucleic acid quantifier.
[0047] (3) Magnetic bead method:
[0048] Centrifugal column method: The centrifugal column method for adsorption of nucleic acids is to place the adsorption column in a collection tube, use a pipette to add all 400μL of the cell lysate obtained in the above step to the adsorption column, let it stand for 2 minutes, and then centrifuge at 12000rpm for 1 minute at room temperature, and pour out the waste liquid in the collection tube. Then put the adsorption column back into the collection tube, add 500μL PW Solution, centrifuge at 10,000rpm for 30s, and pour out the filtrate. Then put the adsorption column back into the collection tube, add 500μL Wash Solution, centrifuge at 10,000rpm for 30s, and pour out the filtrate. Put the adsorption column back into the collection tube, centrifuge at 12000rpm for 2min at room temperature to remove the residual Wash Solution. Finally, take out the adsorption column, put it into a new 1.5mL centrifuge tube, add 50-100μL CE Buffer, let it stand for 3min, centrifuge at 12,000rpm for 2min at room temperature, and collect the DNA solution. The extracted DNA can be used for the next experiment immediately or stored at -20℃.
[0049] (4) Adsorption column method:
[0050] The method for adsorbing nucleic acids by magnetic beads is to add 500μL Buffer MB and 10μL magnetic beads to 400μL of the cell lysate obtained in the above step, mix by pipetting or shaking, and let stand at room temperature for 1min. Place the centrifuge tube on the magnetic rack for 30s, wait for the magnetic beads to be completely absorbed to the tube wall, discard the supernatant, and remove the centrifuge tube from the magnetic rack. Add 900μL 70% ethanol to the centrifuge tube, pipet or shake to mix, place the centrifuge tube on the magnetic rack for 30s, wait for the magnetic beads to be completely absorbed to the tube wall, discard the supernatant, and remove the centrifuge tube from the magnetic rack. Then repeat the above steps once, open the lid and dry at room temperature for 15-20min or open the lid and dry in a 55℃ constant temperature box for 5-7min until there is no liquid residue in the tube. Add 50-100μL TE Buffer to the centrifuge tube, water bath at 65℃ for 5-10min, and mix occasionally. Finally, take out the centrifuge tube and place it on the magnetic rack for 30 seconds. After the magnetic beads are completely absorbed onto the tube wall, carefully pipette the supernatant into a new centrifuge tube to obtain genomic DNA.
[0051] (5) Nucleotide quality detection
[0052] Take 1 μL of DNA extraction product, measure its concentration, A260 and A280 using an ultra-micro nucleic acid quantifier, and calculate the yield (concentration × elution volume) and purity (A260 / A280).
[0053] The extracted genomic DNA was detected by 0.8% agarose gel electrophoresis, with a sample volume of 5 μL and constant voltage electrophoresis of 3-5 V / cm for 2 hours. Observe and take pictures under ultraviolet light with a wavelength of 254 nm. The appearance of a single band of appropriate fragment size in electrophoresis indicates that the DNA integrity is good. Ultra-micro nucleic acid quantification instrument detects A 260 / A 280 The ratio is between 1.7 and 1.9, indicating that the purity of the extracted genomic DNA is good.
[0054] Example 1: Preparation of chitosan-modified attapulgite nucleic acid adsorption rods
[0055] 1. Preparation of chitosan-ATP-PVDF coated nucleic acid adsorption rods:
[0056] The stainless steel wire was ultrasonically cleaned in acetone, ethanol and ultrapure water for 10 min in sequence, and then dried in an oven at 60 ° C for 3 h. The nucleic acid adsorption rod was prepared by the gluing method. 108 mg of chitosan-ATP, 12 mg of PVDF and 200 μL of NMP were mixed and continuously ground until the mixture was fully dispersed and sticky. The pretreated stainless steel wire was manually rotated on a plastic plate with a coating mixture to make the coating evenly distributed. The coating thickness of the fiber can be controlled by controlling the number of coatings to obtain a chitosan-ATP-PVDF coated nucleic acid adsorption rod with a diameter of about 150 μm. Finally, the coated nucleic acid adsorption rod was cured at 80 ° C for 30 min to prepare a chitosan-modified attapulgite nucleic acid adsorption rod. The amount of chitosan-modified attapulgite in each nucleic acid adsorption rod was 0.7 mg.
[0057] 2. Optimization of nucleic acid adsorption rod synthesis conditions
[0058] (1) Taking the ratio of binder to solvent as the factor to be considered:
[0059] The amount of material (chitosan-ATP) added was 54 mg, and the ratios of binder (PVDF) and solvent (NMP) were controlled to be 4.5 mg:100 μL, 5.0 mg:100 μL, 5.5 mg:100 μL, 6.0 mg:100 μL, and 6.5 mg:100 μL, respectively. The adsorption rate of the synthetic material on salmon sperm DNA was used as an evaluation index to detect the effects of different binder and solvent ratios on the adsorption performance of the material.
[0060] (2) Taking the amount of material added as the factor of investigation:
[0061] The amount of solvent (NMP) added was 100 μL, and the ratio of the controlled material (chitosan-ATP) added and the binder (PVDF) was 42.0 mg: 6.0 mg, 45.0 mg: 6.0 mg, 48.0 mg: 6.0 mg, 51.0 mg: 6.0 mg, 54.0 mg: 6.0 mg and 57.0 mg: 6.0 mg. The adsorption rate of the synthetic material on salmon sperm DNA was used as the evaluation index to detect the effect of the material addition amount on the adsorption performance of the material.
[0062] The results are as follows Figure 2 As shown, when the ratio of binder to solvent is 6.0mg:100μL, the chitosan-ATP-PVDF coating material has the highest adsorption rate for DNA; when the ratio of material addition amount to binder is 54.0mg:6.0mg, the chitosan-ATP-PVDF coating material has the highest adsorption rate for DNA. It is determined that the addition amount of chitosan-ATP, binder and solvent is 108mg, 12mg and 200μL respectively.
[0063] Example 2: Chitosan-ATP-PVDF property detection
[0064] 1. X-ray diffraction analysis
[0065] X-ray diffraction analysis (XRD) was performed on chitosan-ATP and nucleic acid adsorption rod coating materials (chitosan-ATP-PVDF), and the chitosan-ATP-PVDF coating was ground into powder, and the crystal structure of the chitosan-ATP-PVDF coating was determined by XRD. The conventional angle scanning was performed at room temperature, the scanning range 2θ was 5° to 80°, and the scanning step length was 0.02° / step.
[0066] The results are as follows Figure 3 As shown, after chitosan-ATP-PVDF was prepared using PVDF as a binder, the structure of chitosan-ATP did not change significantly, indicating that PVDF did not affect the basic crystal structure of chitosan-ATP itself.
[0067] 2. Infrared absorption spectrum analysis
[0068] PVDF, chitosan-ATP and chitosan-ATP-PVDF were analyzed by infrared absorption spectroscopy (FTIR). The chitosan-ATP-PVDF coating was ground into powder. The chemical functional groups of chitosan-ATP-PVDF were determined on a FT-IR instrument using the KBr pellet method in the wave number range of 4000-500 cm -1 KBr was dried at 105 °C for 12 h before use.
[0069] The results are as follows Figure 4 As shown, 1404cm -1The obvious characteristic peak at 3622cm is the vibration absorption peak of difluoromethyl in PVDF. Compared with chitosan-ATP, after the nucleic acid adsorption rod material coating was prepared with PVDF as the binder, chitosan-ATP-PVDF -1 、3543cm -1 、3417cm -1 、1645cm -1 、1033cm -1 、790cm -1 The characteristic peaks at the junction of the chitosan and ATP were still retained. The results showed that using PVDF as a binder did not affect the basic structure of chitosan-ATP.
[0070] 3. Zeta potential test
[0071] The chitosan-ATP-PVDF coating was ground into powder and the charge of ATP under different pH conditions was measured using a Zeta potential meter.
[0072] The results are as follows Figure 5 As shown in the figure, after chitosan-ATP was bonded with PVDF binder, its charge zero point was around pH 6.0-7.0, and the charge zero point of chitosan-ATP was around 6.0. The results showed that PVDF basically did not change the original charge of chitosan-ATP, indicating that PVDF did not change the adsorption properties of chitosan-ATP.
[0073] 4. Scanning electron microscopy analysis
[0074] The surface morphology of chitosan-ATP-PVDF coating was observed by scanning electron microscopy (SEM) analysis.
[0075] The results are as follows Figure 6 As stated, Figure 6 (a) shows that the coating of the chitosan-ATP nucleic acid adsorption rod bonded with PVDF has a uniform morphology and a diameter of about 500 μm. The coating surface is further magnified and observed, as shown in FIG. Figure 6 As shown in (b), the material still retains the original rod-shaped crystal structure of chitosan-ATP, further verifying the analysis results of the structural XRD.
[0076] Example 3: Study on the effect of chitosan-ATP-PVDF nucleic acid adsorption rod on the extraction of pathogenic bacteria genomic DNA
[0077] 1. DNA extraction effect detection
[0078] The genomic DNA of three foodborne pathogens (Escherichia coli, Staphylococcus aureus and Salmonella) was extracted, the cells were broken by an ultrasonic cell disruptor, the DNA was purified using a chitosan-ATP-PVDF nucleic acid adsorption rod, and the amount of extracted genomic DNA was detected. The specific steps are as follows:
[0079] Take 0.5mL of bacteria (10 8 CFU / mL) in a 1.5 mL centrifuge tube, centrifuge at 8000×g for 1 min at room temperature, discard the supernatant, and collect the bacteria. Resuspend the bacterial solution in 400 μL sterile deionized water, use an ultrasonic cell disruptor to disrupt the cells, place the bacteria in an ice water bath, and use intermittent ultrasound (ultrasound 2s, interval 3s, power 50W) for less than 5 minutes to obtain 400 μL of cell lysate containing DNA.
[0080] The nucleic acid adsorption stick adsorption method is:
[0081] Schematic diagram of DNA extraction using chitosan-ATP-PVDF coated nucleic acid adsorption rods Figure 1 As shown, the nucleic acid adsorption rod was immersed in the sample solution (400 μL cell lysate and 70 μL buffer solution) at a speed of 1000 r / min to adsorb DNA.
[0082] The desorption method of nucleic acid adsorption rod is as follows:
[0083] The nucleic acid adsorption rod was transferred to 500 μL of 70% ethanol solution and washed twice. Finally, the nucleic acid adsorption rod was immersed in 100 μL of STPP eluent for 5 min to desorb DNA from the surface of the nucleic acid adsorption rod.
[0084] The results are shown in Table 1. The extraction yields of genomic DNA from Escherichia coli, Staphylococcus aureus and Salmonella were 19.01 μg / mL±0.23 μg / mL, 20.31±0.43 μg / mL and 16.80 μg / mL±0.53 μg / mL, respectively, indicating that this method can obtain a high yield for the extraction of nucleic acids from three different bacteria, showing a high enrichment efficiency for nucleic acids.
[0085] Table 1 Genomic DNA extraction yield
[0086]
[0087]
[0088] The genomic DNA of three foodborne pathogens (Escherichia coli, Salmonella and Staphylococcus aureus) was extracted to investigate the DNA extraction effect of the nucleic acid adsorption rod method in bacterial samples. The electrophoresis results of the products are shown in Figure 2. Figure 7As shown, 1 is the band of Staphylococcus aureus, 2 is the band of Escherichia coli, and 3 is the band of Salmonella. The length of the extracted genomic DNA is greater than 15,000 bp and is a single bright band, indicating that the extracted genomic DNA has good integrity.
[0089] The amplification results of nucleic acid products extracted from three foodborne pathogens (Escherichia coli, Staphylococcus aureus and Salmonella) were analyzed. qPCR was used to evaluate the performance of nucleic acid adsorption rods in extracting genomic DNA. After nucleic acid extraction, qPCR amplification was performed and the cycle threshold (Ct) was recorded. The qPCR reaction conditions were 95℃ pre-denaturation for 3min; 94℃ denaturation for 5s, 60℃ annealing and extension for 40s, and 40 cycles. The reaction system was 2.5μL of 10μmmol / L qPCR premix, 1μL of 10μmol / L upstream and downstream primers, 10μmol / L probe and 2μL template DNA, and water was added to 25μL.
[0090] Ct value: The number of cycles experienced when the fluorescent signal in each reaction tube reaches the set threshold. The amount of DNA extracted by the adsorbent coating is related to the Ct value. The lower the Ct value, the more template DNA is extracted. The efficiency of nucleic acid amplification can be obtained by linear fitting with the logarithmic value of the bacterial genomic DNA concentration as the horizontal axis and the measured Ct value as the vertical axis, as shown in the following formula:
[0091]
[0092] Where: E (%) is the amplification efficiency of the qPCR reaction; Slope is the slope of the standard curve.
[0093] The genomic DNA of Escherichia coli, Staphylococcus aureus and Salmonella was used as the target of qPCR amplification. The results are as follows Figure 8 As shown, the concentration of the bacterial genomic DNA diluted in multiples and the Ct value were linearly fitted, and the R2 values were 0.998, 0.998 and 0.998, respectively, indicating a good linear fit; the amplification efficiencies calculated based on the slopes were 96.69%, 96.14% and 87.18%, respectively. The qPCR amplification efficiency of Escherichia coli and Staphylococcus aureus genomic DNA was greater than 90%, and the amplification efficiency of Salmonella genomic DNA was close to 90%, indicating that the use of nucleic acid adsorption rods to extract nucleic acids in bacterial cultures was effective, and the extracted nucleic acids were suitable for downstream qPCR experiments.
[0094] 2. Detection of extraction effects of different nucleic acid adsorption methods
[0095] The commercially available centrifugal column extraction method, magnetic bead method, and chitosan-ATP were used as controls to detect the extraction effects of different nucleic acid adsorption methods. The method refers to Chinese invention patent application CN202310437817.4. The genomic DNA of Staphylococcus aureus was used as the extraction object, and the DNA extraction effects of chitosan-ATP and chitosan-ATP-PVDF in bacterial samples were investigated as shown in Table 3.
[0096] The results are shown in Table 2. Compared with the commercial column extraction method and magnetic bead method, the chitosan-modified attapulgite extraction method and the chitosan-modified attapulgite nucleic acid adsorption rod had higher DNA yields, which were 22.23±0.78μg and 20.31±0.43μg, respectively. 260 / A 280 The ratio is between 1.7 and 1.9, indicating that the purity of genomic DNA extracted by chitosan-modified attapulgite and chitosan-modified attapulgite nucleic acid adsorption rod is better.
[0097] After conversion, the amount of chitosan-modified attapulgite in patent application CN202310437817.4 is 0.9 mg, which is higher than 0.7 mg in Example 1. At the same time, it was found in the experiment that the chitosan-modified attapulgite extraction method is greatly affected by the operation, the DNA content obtained each time is quite different, and the stability is insufficient; while the chitosan-modified attapulgite nucleic acid adsorption stick has a more stable extraction effect due to the consistent chitosan-modified attapulgite content.
[0098] Table 2 Detection of extraction effect of different nucleic acid adsorption methods
[0099]
[0100] Comparative Example 1: Preparation of chitosan-modified attapulgite nucleic acid adsorption rods using different binders
[0101] On the basis of Example 1, the binder was changed to polytetrafluoroethylene, polyacrylate, and PVDF, respectively, to prepare chitosan-modified attapulgite nucleic acid adsorption rods, and the nucleic acid adsorption effect thereof was tested.
[0102] Table 3 DNA adsorption of adsorption rods prepared with different binders
[0103]
[0104]
[0105] The results show that the chitosan-modified attapulgite nucleic acid adsorption rods prepared using other binders have loose structures and are easy to peel off, making it difficult to adsorb nucleic acids. Even if they can adsorb nucleic acids, the amount of nucleic acid adsorption is small and the adsorption quality is poor.
[0106] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A chitosan-modified attapulgite nucleic acid adsorption stick, characterized in that: The preparation method thereof comprises: Chitosan-modified attapulgite, polyvinylidene fluoride and N-methylpyrrolidone are mixed and ground in a dosage ratio of 50-60 mg: 5-8 mg: 100-150 μL to obtain a mixture; The mixture is coated on a metal wire to obtain an adsorption rod; The chitosan-modified attapulgite nucleic acid adsorption rod was obtained by solidification.
2. The chitosan-modified attapulgite nucleic acid adsorption rod according to claim 1, characterized in that: The coating thickness of the mixture on the adsorption rod is 100-150 μm.
3. The chitosan-modified attapulgite nucleic acid adsorption rod according to claim 1, characterized in that: The preparation method of the metal wire is as follows: ultrasonically clean the metal wire in acetone, ethanol and ultrapure water in sequence for 10 to 20 minutes, and dry it at 60 to 65° C. for 2 to 3 hours.
4. The chitosan-modified attapulgite nucleic acid adsorption rod according to claim 1, characterized in that: The curing is to heat the adsorption rod at 75-85°C for 30-40 minutes.
5. A chitosan-modified attapulgite, the property detection of which includes: X-ray diffraction analysis, infrared absorption spectrum analysis, Zeta potential test, scanning electron microscopy analysis.
6. A chitosan-modified attapulgite nucleic acid adsorption stick, the adsorption method comprising: After the cells were disrupted by an ultrasonic cell disruptor, the nucleic acid adsorption rod was immersed in the sample solution (400 μL cell lysis solution and 70 μL buffer solution) at a speed of 1000 r / min to adsorb DNA.
7. The adsorption method according to claim 5, characterized in that: The genomic DNA of three foodborne pathogens (Escherichia coli, Staphylococcus aureus and Salmonella) was extracted.
8. The adsorption method according to claim 5, characterized in that: The cells were disrupted by ultrasonic cell disruptor at room temperature at 8000×g for 1 min, the supernatant was discarded, the bacteria were collected, and the bacterial solution was resuspended in sterile deionized water. The cells were disrupted by ultrasonic cell disruptor, the bacteria were placed in an ice water bath, and intermittent ultrasonic treatment was performed for less than 5 min to obtain a cell lysate containing DNA.
9. A chitosan-modified attapulgite nucleic acid adsorption stick, wherein the desorption method comprises: The nucleic acid adsorption rod was transferred to 500 μL of 70% ethanol solution for washing twice, and the nucleic acid adsorption rod was immersed in 100 μL of STPP eluent for 5 min to desorb DNA from the surface of the nucleic acid adsorption rod.
10. According to the chitosan-modified attapulgite nucleic acid adsorption rod described in claim 1, the binder is changed to polytetrafluoroethylene, polyacrylate, and PVDF respectively to prepare the chitosan-modified attapulgite nucleic acid adsorption rod, and the nucleic acid adsorption effect is tested, and it is found that PVDF has the best comprehensive adsorption effect.
Citation Information
Patent Citations
Preparation and application of a nucleic acid extraction material of chitosan-modified attapulgite
CN116393105B
Heavy-metal-ion-adsorbing type hybrid flat sheet separation film and preparation method thereof
CN106582306A
Preparation method and applications of attapulgite / polymer porous millimeter-scale small ball
CN106582577A
Preparation and application of nucleic acid extraction material of chitosan modified attapulgite
CN116393105A
Sorption composite membrane and bioseparating device for DNA extraction
RU2631934C1